2017
DOI: 10.4103/jispcd.jispcd_323_17
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vascular endothelial-cadherin in mucoepidermoid carcinoma: Role in cancer development

Abstract: Objectives:Mucoepidermoid carcinoma (MEC) accounts for 35% of all malignant salivary gland tumors. Previous investigations have shown that vasculogenic mimicry (VM) exists in many cancers which can be used as a prognostic factor of poor prognosis. Elevated expression level of vascular endothelial (VE)-cadherin has been implicated in cancer neovascularization, growth, and progression. The current study aimed to study the presence of VE-cadherin in VM channels and tumor cells in different grades of MEC.Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…[ 9 ] In addition, the elevated expression level of VE-cadherin is associated with the cancer growth and progression. [ 16 ] Besides, VE-cadherin is expressed by CSCs and is associated with VM. [ 34 35 ] A study on aggressive melanoma indicated the high expression level of VE-cadherin by cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 9 ] In addition, the elevated expression level of VE-cadherin is associated with the cancer growth and progression. [ 16 ] Besides, VE-cadherin is expressed by CSCs and is associated with VM. [ 34 35 ] A study on aggressive melanoma indicated the high expression level of VE-cadherin by cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of positive cells for biomarkers was graded as follows: 1 (weak) for <20% positive cells, 2 (moderate) for 20%–50% positive cells, and 3 (strong) for >50% positive cells. [ 16 ]…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor growth and metastasis are correlated to the function and the altered expression level of many proteins, as well as gene mutations (5,8,(22)(23)(24). In addition, cancer cell invasion and metastasis are correlated to the level of cancer cell differentiation.…”
Section: Introductionmentioning
confidence: 99%